The didactic sequence as a strategy for strengthening metric thinking, through the use of the home-school garden and the PhET - Lagos López, Yicela Heredia; González Pulido, José Weymar (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of this research was the implementation of didactic sequences, to strengthen metric thinking, through the use of the home garden and PHETs, based on the need it presents in the insufficiencies and low level of performance evidenced in ninth grade students 902 and 906, in the 2017-2018 saber tests, at the Leonor Álvarez Pinzón Higher Normal School Educational Institution. Located in the Municipality of Tunja, in terms of mathematical skills, communication, representation and modeling, reasoning and argumentation, and problem posing and solving. The study focused on strengthening metric thinking. The construction of the theoretical framework that supports the research is metric mathematical thinking. The methodology used is research - action, under the gaze of the qualitative approach. Similarly, a sample of 76 students from grades 902 and 906 were taken as research subjects. Said proposal will be executed in three application phases. Diagnostic phase to identify the level of development of metric thinking in students. Pedagogical intervention phase, with a proposal of the didactic sequences for strengthening the area, perimeter, problem solving and finally the evaluation phase through a closing test, in order to assess the impact of the research-action strategy developed.